PROFILE OF 10th GRADE HIGH SCHOOL STUDENTS MISCONCEPTION ON VIRUS TOPIC BASED ON THREE-TIER MULTIPLE CHOICE DIAGNOSTIC TEST - Ningtyas, Listya Eka; Asri, Mahanani Tri (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2021)
Biology learning is closely tied to concepts. Misconceptions arise within learning of several fundamental biological principles. One of the biology topics frequently faces misconceptions is viruses. To recognize misconceptions in students, the three-tier multi-choice diagnostic test method is important to be used. This research was intended to explain the misconception of students, the percentage of student misconception and the source of virus topic misconception in high school. This research was a multi-stage qualitative descriptive research, including the preparation of a three-tier multi-choice diagnostic test instrument, the validation of instruments, conducting student observations, conducting interviews with the students, the analysis of data and the assessment of outcomes. This research was performed at 10 th grade High School with as many as 36 students receiving virus topic. Results showed that 5.43% of students encountered positive misconceptions, 6.88% students encountered negative misconceptions, 30.56% students encountered misconception. Total misconceptions showed that 42.87% of students encountered misconception of virus topic. The highest misconception was found in the concept of bacteriophage reproduction, which had the largest misconception of 49.07%. The lowest misconception was found in the concept of the role of viruses, which had the smallest misconception of 36.8%. The highest misconception was found in the indicator of Identifying the way the virus lives in the host cell, which had the largest misconception of 63.89%, while the lowest was 19.44% in the indicator of identifying the role of viruses that are beneficial to human life. The aspects that contributed to the misconception were inadequate books, restricted choice of learning approaches during the Covid-19 pandemic, and context errors faced by students. Keywords: profile, misconception, virus topic, three-tier diagnostic test.